PENGARUH PARTISIPASI ANGGARAN TERHADAP SENJANGAN ANGGARAN DENGAN BUDAYA ORGANISASI, GAYA KEPEMIMPINAN, ASIMETRI INFORMASI, LOCUS OF CONTROL DAN KETIDAKPASTIAN LINGKUNGAN SEBAGAI VARIABEL MODERASI (Studi Empiris Rumah Sakit Umum Pemerintah di Kota Padang) - Rizky Nusari Cindy; Darlis Edfan; Julita Julita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
The purpose of this research was to identify and analyze about (1) The effect ofbudgetary participation on budgetary slack with organizational cultural as moderatingvariable, (2) The effect of budgetary participation on budgetary slack with leadershipstyle as moderating variable, (3) The effect of budgetary participation on budgetary slackwith information asymmetry as moderating variable, (4) The effect of budgetaryparticipation on budgetary slack with locus of control as moderating variable, (5) Theeffect of budgetary participation on budgetary slack with environmental uncertainty asmoderating variable. Study was conducted at government general hospital in PadangCity, which amount to 7 general hospital. The data used in this research was primarydata with questionnaire as an instrument. The method that used to the sample selectionwas nonprobability sampling. The number of samples in this research were 120respondents. Hypothesis test used in this research was statistical t-test. Data analysistechniques used in this research was multiple linear regression analysis using StatisticalProduct and Service Solution (SPSS) version 23.0 for Windows as data processingsoftware program. Results of hypothesis test using statistical t-test showed the significantvalue of organizational cultural variable 0.006 < 0.05 which means that H1 accepted, theleadership style variable 0.012 < 0.05 which means that H2 accepted, informationasymmetry variables 0.008 < 0.05 which means the H3 accepted, locus of controlvariables 0.001 < 0.05 which means the H4 accepted, and environmental uncertaintyvariables 0.001 < 0.05, which means the H5 accepted. The results showed organizationalcultural, leadership style, information asymmetry, locus of control and environmentaluncertainty has effect on budgetary slack.Keywords : Budgetary Participation, Budgetary Slack, Organizational Cultural,Leadership Style, Information Asymmetry, Locus of Control andEnvironmental Uncertainty.